Determinan Net Interest Margin pada Bank Perkreditan Rakyat Indonesia - Nindhita Rafianti Putri; Adyanto Budi Rachmansyah; Rahmat Setiawan (Jurnal Riset Bisnis dan Manajemen, 2019)
The purpose of this research is to analyze the determinants of net interest margin (NIM) at Bank Perkreditan Rakyat (BPR) or rural banks in Indonesia 2016. This research uses multiple linear regression model. Data was obtained from Infobank magazine published in July 2016-2017. This research uses 269 BPR or rural banks in Indonesia. Dependent variable in this research is Net Interest Margin (NIM). Independent variables use credit risk proxied with non-performing loan (NPL), liquidity risk proxied by loan to deposit ratio (LDR), capital adequacy proxied with capital adequacy ratio (CAR), the efficiency ratio proxied by BOPO, and bank size proxied by logarithm of total asset (SIZE). The results showed that liquidity risk, and capital adequacy have significant positive affect on net interest margin while the credit risk, efficiency ratio, and bank size affect inversely on net interest margin